Analysis of thumbprint recognition in different bit levels - Md. Rezaur, Rahman; Bong, David B L; Lee, T.Z (IEEE, 2013)
In this paper, a preliminary analysis of thumbprint recognition in different bit levels is presented. A digital image consists of m x n pixels and each pixel is represented by gray level value. In an 8-bits gray level image, the gray level value range from 0 to 255 for each pixel. Each bit-plane will then be extracted as the input into the neural network to test its performance and accuracy. The performance is then evaluated based on the recognition rate of each bit plane